2001
DOI: 10.1021/la001023u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Adsorption of Long-Chain Alkylamines on Silicates:  A Spectroscopic Study. 2. Albite

Abstract: Using FTIR (DRIFTS and IRRAS) and XPS spectroscopy, ζ potential measurements, and Hallimond flotation tests, we confirmed that long-chain primary amines are adsorbed on silicates at pH 6-7 through the 2D-3D precipitation mechanism. The orientation and packing of dodecyl-and hexadecylammonium acetate and chloride adsorbed on albite in the different regions of the adsorption isotherm were determined. It was shown that these characteristics depend strongly on the substrate. Coadsorption of the counterion was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…4a, center). A similar phase transition was observed by Chernyshova et al [48] when studying the dodecylamine salts adsorption of on silicates. When this monoamine is adsorbed below the concentration of 2×10 −5 M, the alkyl chains are chaotically oriented and the distances between the amine ions on the surface are large.…”
Section: Effect Of Ad N Adsorption On Nps Aggregationsupporting
confidence: 82%
See 1 more Smart Citation
“…4a, center). A similar phase transition was observed by Chernyshova et al [48] when studying the dodecylamine salts adsorption of on silicates. When this monoamine is adsorbed below the concentration of 2×10 −5 M, the alkyl chains are chaotically oriented and the distances between the amine ions on the surface are large.…”
Section: Effect Of Ad N Adsorption On Nps Aggregationsupporting
confidence: 82%
“…When this monoamine is adsorbed below the concentration of 2×10 −5 M, the alkyl chains are chaotically oriented and the distances between the amine ions on the surface are large. Whereas above this critical value, the chains adopt a perpendicular orientation forming well-packed patches on the silicate [48]. Therefore, as the concentration is raised above C 2 , a full coverage of NPs is reached, and both the interchain interactions and the extension of each chain increase, leading finally to a higher and well-defined packing order.…”
Section: Effect Of Ad N Adsorption On Nps Aggregationmentioning
confidence: 99%
“…It has been cited in the literature extensively that the amines are sensitive to fine particles (slimes) and desliming is an essential step prior to silicate flotation with amines. Our recent spectroscopic studies of amine interaction on silicate surfaces showed that the ammonium groups adsorb through hydrogen bonding on surface silanol groups as well as electrostatic interactions (29,30). The infrared spectra (DRIFT) of quartz and albite treated with increasing amine concentration showed a progressive diminishing of silanol groups, signifying amine interaction with silanols through hydrogen bonding.…”
Section: Diffuse Reflectance Ftir Studiesmentioning
confidence: 97%
“…The oxyhydryl collectors adsorb on oxide, silicate and salt-type minerals either physically by electrostatic interactions and/or chemically, while the amine collectors adsorb on silicates purely by electrostatic interactions. However, our spectroscopic studies [26,27] of the adsorption of primary alkyl amine on silicate surface revealed that the ammonium head groups are H-bonded to the negatively charged silanols as H | ≡Si-O· · ·H-N + H 2 -R and establishing the following equilibrium when the local concentration approaches a critical value:…”
Section: Diffuse Reflectance Ftir Studiesmentioning
confidence: 98%